Composite insulation layer structure for high-temperature-resistant low-smoke halogen-free cable and forming method

CN122991736APending Publication Date: 2026-10-27JIANGSU DONG PHOTOELECTRICITY XIAN CABLE CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611401363.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

1.本申请通过过渡内层的硅烷接枝改性实现层间界面高强度粘接,同时依托弹性基体的形变缓冲作用,有效吸收冷热循环过程中层间产生的剪切内应力,解决了传统双层结构界面结合薄弱、易产生微裂纹及分层剥离的缺陷,大幅提升绝缘层界面可靠性与长期服役稳定性,同时可适度降低三层共挤对机头同心度的精度要求,降低量产调试难度,提升产品批次一致性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122991736A_ABST
    Figure CN122991736A_ABST
Patent Text Reader

Abstract

The application relates to a high-temperature-resistant low-smoke halogen-free cable composite insulation layer structure and a forming method, and relates to the technical field of cable insulation layers. The composite insulation layer structure is coated on the outside of a conductor and is composed of an integrated structure of a transition layer, a functional layer and a fire-resistant layer from the inside to the outside. Each layer is a halogen-free high polymer extrusion layer, and no mica wrapping layer is arranged on the outside. The three-layer inorganic filler filling amount is distributed in a gradient increasing mode, and the high filling amount is concentrated in the outer layer. The forming method coats the insulation layer structure on the surface of the conductor through one-time co-extrusion of a three-layer co-extrusion die head, and then is crosslinked and formed through synchronous electron beam irradiation. The application solves the problems of weak interface bonding force, easy delamination, poor flexibility under high filling, fire risk and the like of the existing cable insulation layer; improves the interface bonding strength and reliability, coordinates the fire resistance and flexibility, eliminates the fire risk, and simplifies the production process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of cable insulation technology, and in particular to a composite insulation layer structure and molding method for high-temperature resistant, low-smoke, halogen-free cables. Background Technology

[0002] With the rapid development of new energy, rail transit, and special equipment, comprehensive requirements have been placed on cables for long-term high temperature resistance, low smoke halogen-free flame retardancy, fire resistance, and excellent machinability. Existing high-temperature resistant, low-smoke halogen-free cable insulation mainly adopts single-layer extruded insulation, double-layer step-extruded insulation, double-layer co-extruded composite insulation, and composite structures with fire-resistant wrapping tape added to the insulation layer.

[0003] For example, patent CN208444644U discloses a high-temperature resistant double-layer co-extruded low-smoke halogen-free fire-resistant cross-linked wire. It uses double-layer co-extrusion molding with 125℃ irradiated cross-linked low-smoke halogen-free composite insulation, separating electrical insulation and flame-retardant functions into layers. However, this structure relies solely on the natural melting and bonding of the melt, without any reinforcement design for the interlayer interface. Due to the difference in thermal expansion between the inner and outer layers, micro-cracks easily develop at the interface under alternating hot and cold conditions. The outer layer uses high inorganic filler to achieve flame retardancy, resulting in insufficient material toughness. Furthermore, double-layer co-extrusion places stringent requirements on the concentricity control of the die head, leading to significant fluctuations in mass production performance. Patent CN212010402U... A halogen-free, low-smoke, high-performance wire is disclosed, which adopts a step-extrusion double-layer insulation structure. The outer layer uses ceramicized polyolefin to achieve fire resistance. However, the step-extrusion process exposes the inner semi-finished product to the environment, and the interface is easily contaminated with dust and moisture. The interlayer adhesion is weak, and it is easy to delaminate when heated and bent. In addition, the process is complicated and the production cost is high. The patent with publication number CN215496123U discloses a low-smoke, fire-resistant, and flame-retardant cable for rail transit. It relies on mica tape to physically wrap to achieve fire protection. The insulation layer does not have fire resistance. There are gaps between the layers of the cable, which can easily cause flame spread. When the cable is bent, the mica tape is easy to crack and shift. In addition, the extra wrapping process reduces production efficiency.

[0004] In summary, existing high-temperature, low-smoke, halogen-free cable composite insulation technologies still have many shortcomings: Existing double-layer composite insulation relies solely on the natural bonding of the melt, lacking interface reinforcement design. Due to the difference in thermal expansion coefficients between the inner and outer layers, micro-cracks and delamination easily occur between the insulation layers under thermal cycling and mechanical bending conditions, resulting in insufficient reliability of the insulation interface. Traditional fire-resistant solutions rely on external physical wrapping structures such as mica tape for fire resistance, but the fire resistance of the insulation itself is weak. Gaps between layers easily lead to longitudinal flame propagation, and the wrapping tape is prone to cracking and displacement failure when the cable is bent. To achieve flame retardancy and fire resistance, the insulation layer requires high levels of inorganic fillers, resulting in a hard and brittle material matrix, reduced cable bending resistance and low-temperature cracking resistance, and difficulty in achieving a balance between temperature resistance, electrical insulation, flame retardancy, fire resistance, and mechanical properties. Stepwise extrusion processes easily cause insulation interface contamination. Double-layer co-extrusion places stringent requirements on die head concentricity and mold precision, making mass production debugging difficult and product consistency hard to guarantee.

[0005] Therefore, there is an urgent need to develop a composite insulation layer structure and molding method for high-temperature resistant, low-smoke, halogen-free cables to solve the above-mentioned technical problems. Summary of the Invention

[0006] Based on this, it is necessary to provide a composite insulation layer structure and molding method for high-temperature resistant, low-smoke, halogen-free cables to address the above-mentioned technical problems. By combining a three-layer gradient composite insulation integrated co-extrusion structure with an overall irradiation cross-linking process, the interlayer micro-cracks and delamination hazards are eliminated, the body becomes fire-resistant, the defects of cross-ignition in the mica wrapping gap are removed, the insulation reliability and mass production consistency are greatly improved, the process is simplified, and the cost is reduced.

[0007] This application provides a composite insulation layer structure for high-temperature resistant, low-smoke, halogen-free cables, employing the following technical solution: A composite insulation layer structure for high-temperature resistant, low-smoke, halogen-free cables is disclosed, covering the outside of the conductor. From the inside out, it consists of a transition layer, a functional layer, and a fire-resistant layer, forming an integrated composite insulation layer structure. Each layer of the composite insulation layer structure is a halogen-free polymer extrusion layer. No mica fire-resistant wrapping layer is provided on the outer side of the composite insulation layer structure. The transition layer comprises an ethylene-vinyl acetate copolymer-polyolefin elastomer blend matrix, a silane-grafted polyolefin, and a first inorganic filler; The functional layer comprises an irradiated cross-linked polyolefin elastomer-ethylene-butyl acrylate copolymer blend resin, a phosphorus-nitrogen synergistic flame retardant, and a second inorganic filler; The refractory layer comprises a polyolefin elastomer matrix and a third inorganic filler, wherein the third inorganic filler comprises low-melting-point borosilicate glass powder and metal hydroxide; The composite insulation layer structure consists of three layers of inorganic fillers with gradually increasing amounts from the inside out. Based on the total mass of each layer, the first inorganic filler accounts for 25-35 wt% of the total mass of the transition layer, the second inorganic filler accounts for 40-48 wt% of the total mass of the functional layer, and the third inorganic filler accounts for 50-58 wt% of the total mass of the refractory layer.

[0008] By adopting the above technical solution, the silane-grafted polyolefin in the transition layer contains hydrolyzable silane groups, which can chemically bond with the polymer chains of adjacent layers under high-temperature co-extrusion conditions, forming an interfacial bridging effect and significantly improving the interlayer bonding strength. Simultaneously, the blend matrix of ethylene-vinyl acetate copolymer and polyolefin elastomer endows the transition layer with excellent flexibility and elastic deformation capacity, effectively absorbing and buffering interfacial shear stress caused by differences in the thermal expansion coefficients of each layer under alternating hot and cold conditions, preventing the initiation and propagation of interfacial microcracks. The functional layer, as the main insulation layer, uses a blend resin of irradiated cross-linked polyolefin elastomer-ethylene-butyl acrylate copolymer as the matrix, possessing both excellent high-temperature electrical insulation properties and oil and aging resistance. Combined with phosphorus and nitrogen synergistic flame retardants, it achieves efficient gas-phase and condensed-phase flame retardancy. In the refractory layer, low-melting-point borosilicate glass powder melts under high-temperature flame to form a dense ceramic protective layer, effectively isolating heat and oxygen from entering the interior, giving the insulation layer structure intrinsic fire resistance without relying on external mica wrapping tape. The three-layer inorganic filler is designed with a gradient increase from the inside to the outside. This design ensures that the inner and middle layers retain sufficient polymer elastic matrix to guarantee flexibility and mechanical strength, while the outer layer concentrates a high-filling inorganic system to achieve efficient flame retardancy and fire resistance. This simultaneously optimizes electrical insulation, flame retardancy and fire resistance, and mechanical properties.

[0009] Preferably, the thickness of the transition layer is 0.15-0.30 mm, the thickness of the functional layer is 0.4-1.2 mm, and the thickness of the fire-resistant layer is 0.2-0.4 mm.

[0010] By adopting the above technical solutions, the thickness of the transition layer is controlled within the range of 0.15-0.30mm, ensuring sufficient interfacial bonding layer thickness and stress buffering capacity while avoiding excessive thickness that would increase the overall outer diameter of the insulation layer and raise material costs. The functional layer thickness is 0.4-1.2mm, serving as the main insulation layer and undertaking the primary electrical insulation and voltage withstand functions. This thickness range ensures that the cable has sufficient insulation safety margin under rated operating voltage, while also taking into account the cable's bending flexibility. The fire-resistant layer thickness is 0.2-0.4mm, which is sufficient to accommodate a sufficient amount of low-melting-point borosilicate glass powder and metal hydroxides to ensure ceramic shell formation and flame-retardant and smoke-suppressing performance under flame conditions. On the other hand, it avoids excessive outer layer thickness that would lead to excessive cable bending stiffness and reduced heat dissipation performance. The above-mentioned synergistic matching relationship of the three layer thicknesses achieves the best balance between electrical performance, fire protection, and mechanical flexibility in the composite insulation layer.

[0011] Preferably, the first inorganic filler is surface-activated aluminum hydroxide; by weight percentage, the transition layer comprises the following components: 42-50 wt% ethylene-vinyl acetate copolymer-polyolefin elastomer blend matrix, 7-12 wt% silane-grafted polyolefin, 3-6 wt% compatibilizer, 1-2 wt% composite antioxidant, 1-2 wt% crosslinking sensitizer, and 25-35 wt% surface-activated aluminum hydroxide; wherein, the mass ratio of ethylene-vinyl acetate copolymer to polyolefin elastomer in the ethylene-vinyl acetate copolymer-polyolefin elastomer blend matrix is ​​60:40-70:30, and the silane-grafted polyolefin is vinyltrimethoxysilane-grafted polyethylene.

[0012] By adopting the above technical solution, the amount of silane-grafted polyolefin added in the transition layer is 7-12 wt%. This ratio ensures sufficient grafting active sites to form interfacial chemical bonds with adjacent layers, resulting in strong interlayer bonding, while avoiding excessive silane components that could lead to excessive cross-linking of the matrix and loss of elastic buffering function. The ethylene-vinyl acetate copolymer and polyolefin elastomer are blended at a mass ratio of 60:40-70:30, giving the matrix both the good polarity and processing fluidity of the ethylene-vinyl acetate copolymer and the high elasticity and low-temperature resistance of the polyolefin elastomer. This ensures that the transition layer has excellent compatibility and interfacial wettability when bonded to layers of different polarities on both the inner and outer sides. The surface-activated aluminum hydroxide, after surface modification with a coupling agent, significantly enhances the interfacial bonding force with the polymer matrix, improves dispersion uniformity, and avoids localized stress concentration caused by inorganic particle agglomeration. Simultaneously, the aluminum hydroxide releases water of crystallization upon thermal decomposition, providing some initial flame retardancy and cooling effects. The addition of compatibilizers further improves the interfacial compatibility between polar inorganic fillers and non-polar polymer matrix, while composite antioxidants ensure the transition layer's resistance to thermo-oxidative aging during high-temperature extrusion and long-term use. Crosslinking sensitizers provide sensitization and promotion functions for subsequent irradiation crosslinking.

[0013] Preferably, the second inorganic filler is a magnesium hydroxide and aluminum hydroxide compound with a mass ratio of magnesium hydroxide to aluminum hydroxide of 3:2; by weight percentage, the functional layer comprises the following components: 38-46 wt% irradiated crosslinked polyolefin elastomer-ethylene-butyl acrylate copolymer blend resin, 6-9 wt% phosphorus-nitrogen synergistic flame retardant, 40-48 wt% surface-activated magnesium hydroxide and aluminum hydroxide compound, 1-2 wt% anti-thermal-oxidative aging agent, and 1-2 wt% crosslinking sensitizer; wherein, the mass ratio of polyolefin elastomer to ethylene-butyl acrylate copolymer in the polyolefin elastomer-ethylene-butyl acrylate copolymer blend resin is 50:50-70:30, and the phosphorus-nitrogen synergistic flame retardant is a compound of piperazine pyrophosphate and melamine polyphosphate.

[0014] By adopting the above technical solution, the functional layer uses a compound metal hydroxide with a mass ratio of magnesium hydroxide to aluminum hydroxide of 3:2 as the second inorganic filler. The decomposition temperature of magnesium hydroxide is about 340℃, and that of aluminum hydroxide is about 200℃. The compound of the two can absorb heat and release water vapor in stages over a wide temperature range, achieving a gradient thermal protection effect. At the same time, the magnesium oxide layer formed after the decomposition of magnesium hydroxide has a better char-forming enhancement effect. The phosphorus-nitrogen synergistic flame retardant is a compound of piperazine pyrophosphate and melamine polyphosphate. When heated, phosphorus and nitrogen work synergistically: the phosphorus component promotes char formation, and the nitrogen component releases non-flammable gases to dilute the concentration of combustible volatiles. Together with the heat absorption and cooling effect of the metal hydroxide, they form a multiple flame retardant mechanism, enabling the functional layer to achieve excellent flame retardant and smoke suppression performance with a medium filling amount (40-48wt%). In irradiated crosslinked polyolefin elastomer-ethylene-butyl acrylate copolymer blends, the ethylene-butyl acrylate copolymer contains polar ester groups, which have good affinity with metal hydroxide inorganic fillers, while also imparting good oil resistance and low-temperature toughness to the material. The polyolefin elastomer provides high elasticity and processing fluidity. The two are blended in a 50:50-70:30 ratio to achieve complementary properties. Thermo-oxidative aging resistant agents improve the insulation resistance retention and mechanical property retention of the functional layer under long-term high-temperature service conditions.

[0015] Preferably, the metal hydroxide in the refractory layer is a magnesium hydroxide and aluminum hydroxide compound with a mass ratio of magnesium hydroxide to aluminum hydroxide of 1:1; by weight percentage, the refractory layer comprises the following components: 32-38 wt% polyolefin elastomer matrix, 28-34 wt% low-melting-point borosilicate glass powder, 22-26 wt% magnesium hydroxide and aluminum hydroxide compound, 3-6 wt% elastic toughening agent, and 1-3 wt% crosslinking sensitizer; wherein the low-melting-point borosilicate glass powder has a softening point of 450-550℃ and a particle size of 5-15 μm.

[0016] By adopting the above technical solution, the addition amount of low-melting-point borosilicate glass powder in the refractory layer is 28-34 wt%. The softening point of this glass powder, 450-550℃, matches the temperature range of cable fires. When the flame temperature reaches the softening point of the glass powder, the glass powder particles melt and foam and expand under the action of water vapor released by the decomposition of metal hydroxide, forming a continuous and dense ceramic barrier layer, effectively blocking the transfer of flame heat to the interior. The particle size of the borosilicate glass powder is controlled within the range of 5-15 μm, ensuring both uniform dispersion of particles in the matrix and rapid spreading to form a continuous ceramic layer after melting. The metal hydroxide adopts a compound system of magnesium hydroxide and aluminum hydroxide in a mass ratio of 1:1, which works synergistically with the glass powder: the early decomposition of metal hydroxide absorbs heat and cools the temperature, and the released water vapor dilutes the combustible gas. At the same time, the decomposition products interact with the molten glass powder to promote the ceramicization reaction, improving the density and structural strength of the ceramic layer. The polyolefin elastomer matrix imparts good flexibility to the refractory layer, while the elastic toughening agent further absorbs the brittle stress introduced by the inorganic fillers, ensuring sufficient flexural strength at room temperature and preventing cracking caused by high inorganic filler content. The total amount of inorganic fillers in the refractory layer reaches 50-58 wt%, fully guaranteeing the material basis for ceramic reaction under flame conditions.

[0017] Furthermore, this application also provides a molding method for preparing the composite insulation layer structure for high-temperature resistant, low-smoke, halogen-free cables as described in any of the above claims, employing the following technical solution: A molding method includes the following steps: S1. The components used to prepare the transition layer, functional layer and refractory layer are co-extruded onto the conductor surface in one step through a three-layer co-extrusion die head to form a three-layer composite insulation layer preform. S2. Cool and shape the three-layer composite insulation layer blank obtained in S1 to obtain a three-layer composite insulation layer semi-finished product. S3. The three-layer composite insulation layer semi-finished product obtained in S2 is subjected to three-layer synchronous electron beam irradiation crosslinking. The three-layer composite insulation layer is simultaneously irradiated and crosslinked to form a three-dimensional crosslinked network. Among them, the crosslinking degree of the transition layer after irradiation is 45-55%, the crosslinking degree of the functional layer is 60-70%, and the crosslinking degree of the fire-resistant layer is 50-60%.

[0018] By adopting the above technical solution, S1 employs a three-layer co-extrusion die head for one-time co-extrusion molding. The three layers of melt converge and simultaneously coat the conductor surface within the extrusion die. The layers adhere tightly to each other in a high-temperature molten state, utilizing the mutual diffusion and entanglement of polymer chain segments between the layers to form a physical bond. Simultaneously, the silane graft groups in the transition layer chemically bond with the polymer active sites of adjacent layers at the extrusion temperature, achieving a dual interface enhancement effect of physical entanglement and chemical bonding. This one-time co-extrusion process eliminates the risk of interface contamination caused by the exposure of semi-finished products to the environment during step extrusion, ensuring the consistency and reliability of the interlayer bonding quality. In S2, cooling and shaping allow the three layers of melt to solidify in an orderly manner, fixing the thickness and concentricity of each layer. In S3, electron beam irradiation is used to simultaneously crosslink the three-layer composite insulation layer. Unlike traditional chemical crosslinking, which requires high temperature and high pressure and is prone to generating byproducts, electron beam irradiation crosslinking is completed at room temperature, the degree of crosslinking is precisely controllable, and no small molecule byproducts are released. The simultaneous crosslinking of the three layers enables each layer to form a synergistic three-dimensional network structure during the crosslinking process. The polymer chains at the interlayer interfaces generate cross-linking bonds through co-irradiation, further enhancing the interfacial bonding strength. The crosslinking degree of the transition layer is controlled at 45-55%, the functional layer at 60-70%, and the fire-resistant layer at 50-60%. The differentiated crosslinking degree design allows each layer to achieve optimal performance balance: moderate crosslinking of the transition layer maintains elastic buffering capacity, high crosslinking degree of the functional layer ensures dimensional stability and insulation retention at high temperatures, and moderate crosslinking degree of the fire-resistant layer maintains sufficient flexibility to adapt to cable bending while ensuring structural strength.

[0019] Preferably, in S1, the three-layer co-extruder is a series type or a three-layer distributor type, and the co-extrusion temperature of the three-layer co-extruder head is 140-180℃.

[0020] By adopting the above technical solution, the co-extrusion temperature is controlled within the range of 140-180℃, ensuring that each layer of polymer material is fully melted and plasticized, possessing good fluidity to form a uniform thickness and smooth surface, while avoiding excessively high temperatures that could lead to premature hydrolysis and cross-linking of silane-grafted polyolefins or thermal decomposition and deactivation of phosphorus-nitrogen synergistic flame retardants. Both series-type and three-layer distributor-type die head forms can achieve uniform convergence and concentric coating of the three layers of melt, adapting to the configuration requirements of different cable specifications and production lines.

[0021] Preferably, in S2, the cooling and shaping process adopts a segmented water cooling method, which involves gradual cooling through an 80°C warm water section and a 25°C cold water section.

[0022] By adopting the above technical solution and employing a segmented water-cooling gradual cooling method, the three-layer molten material is first slowly cooled and solidified in an 80°C warm water section, avoiding the concentration of interlayer thermal stress and the generation of interfacial microcracks caused by rapid cooling. Subsequently, it is further cooled to room temperature in a 25°C cold water section. This gradual cooling process ensures that the thermal shrinkage of each layer proceeds smoothly, utilizing the elastic buffering effect of the transition layer to release cooling internal stress, effectively guaranteeing the dimensional stability and interlayer bonding integrity of the three-layer composite insulation layer.

[0023] Preferably, in S3, by using the same type of crosslinking sensitizer but with different amounts in the formulations of the transition layer, functional layer, and refractory layer, the three-layer composite insulation layer can obtain different degrees of crosslinking; the crosslinking sensitizer is triallyl isocyanurate.

[0024] By employing the above technical solution, triallyl isocyanurate, as an irradiation crosslinking sensitizer, contains multiple allyl double bonds in its molecular structure. Under electron beam irradiation, it can rapidly generate free radicals and participate in the crosslinking reaction, effectively improving the irradiation crosslinking efficiency. By adding different mass proportions of triallyl isocyanurate to the formulations of the transition layer, functional layer, and refractory layer, different crosslinking reactivity is obtained in the three layers under the same irradiation dose, thereby achieving differentiated crosslinking degrees. This solution eliminates the need for zoned control of the irradiation process; a single irradiation parameter can achieve differentiated crosslinking of the three layers, simplifying process control and ensuring good consistency in mass production.

[0025] Preferably, in S3, the irradiation dose of the three-layer synchrotron electron beam crosslinking is 80-120 kGy.

[0026] By adopting the above technical solution, the irradiation dose is controlled within the range of 80-120 kGy. At this dose, combined with the amount of crosslinking sensitizer added to each layer's formulation, the target crosslinking degree ranges of 45-55% for the transition layer, 60-70% for the functional layer, and 50-60% for the refractory layer can be achieved, respectively. This irradiation dose has both economic and efficiency advantages, avoiding the problems of insufficient crosslinking, inadequate heat resistance, and insufficient mechanical strength caused by too low a dose, while also avoiding the risks of excessive crosslinking embrittlement and decreased insulation performance caused by too high a dose.

[0027] In summary, this application includes the following beneficial technical effects: 1. This application achieves high-strength interlayer bonding through silane grafting modification of the transition inner layer. At the same time, relying on the deformation buffering effect of the elastic matrix, it effectively absorbs the shear stress generated between the layers during the thermal cycle, solving the defects of weak interlayer bonding, easy generation of microcracks and delamination in traditional double-layer structures. It significantly improves the reliability of the insulation layer interface and the stability of long-term service. At the same time, it can appropriately reduce the precision requirements of the die head concentricity in three-layer co-extrusion, reduce the difficulty of mass production debugging, and improve the consistency of product batches.

[0028] 2. This application eliminates the traditional external wrapping structure of mica tape, relying on the fire-resistant outer layer to achieve fire protection of the body. There are no physical assembly gaps between the layers, eliminating the longitudinal flame propagation channel, avoiding the risk of mica tape bending, cracking, displacement and failure, simplifying the production process, effectively improving production efficiency and reducing production costs, while avoiding excessive increase in cable outer diameter, and adapting to the laying scenario in narrow space.

[0029] 3. This application adopts a structural design with an increasing inorganic filler gradient from the inside to the outside, concentrating the high filler fire-resistant and flame-retardant system in the outer layer, while the inner layer and the main insulation layer retain the complete polymer elastic matrix. This effectively solves the material hardness and brittleness defects caused by high filler, significantly improves the cable's bending resistance and low-temperature cracking resistance, breaks through the technical barriers of mutual restraint between the high temperature resistance, electrical insulation, flame retardancy and fire resistance and mechanical properties of traditional insulation materials, and achieves synergistic optimization of multiple core performances.

[0030] 4. This application adopts a three-layer integrated synchronous co-extrusion and overall synchronous irradiation cross-linking molding process, abandoning the step-by-step extrusion process, and completely eliminating the contamination of the insulation interface with dust, water vapor and other impurities, ensuring the quality of interlayer fusion bonding; the three-layer synchronous cross-linking makes the overall structural performance uniform and stable, further improving the high temperature aging resistance, electrical insulation and overall structural stability of the composite insulation layer, and adapting to the high-end and harsh working conditions of new energy, rail transit, special equipment and other applications. Attached Figure Description

[0031] Figure 1 This is a schematic diagram of the composite insulation layer structure for high-temperature resistant, low-smoke, halogen-free cables of this application.

[0032] Figure 2 This is a schematic diagram of the molding method of this application.

[0033] Explanation of reference numerals in the attached drawings: 00, conductor; 10, insulation layer structure; 11, transition layer; 12, functional layer; 13, fire-resistant layer. Detailed Implementation

[0034] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0035] Reference Figure 1 This application provides a composite insulation layer structure for high-temperature resistant, low-smoke, halogen-free cables, which covers the outside of the conductor 00 and consists of a transition layer 11, a functional layer 12, and a fire-resistant layer 13 from the inside to the outside. The three layers constitute an integrated composite insulation layer structure 10. Each layer of the composite insulation layer structure 10 is a halogen-free polymer extrusion layer. The composite insulation layer structure 10 does not have a mica fire-resistant wrapping layer on the outside.

[0036] Reference Figure 2 This application also provides a molding method for preparing the composite insulation layer structure for high-temperature resistant, low-smoke, halogen-free cables as described in any of the above claims, comprising the following steps: S1. The components used to prepare the transition layer, functional layer and refractory layer are co-extruded onto the conductor surface in one step through a three-layer co-extrusion die head to form a three-layer composite insulation layer preform. S2. Cool and shape the three-layer composite insulation layer blank obtained in S1 to obtain a three-layer composite insulation layer semi-finished product. S3. The three-layer composite insulation layer semi-finished product obtained in S2 is subjected to three-layer synchronous electron beam irradiation crosslinking. The three-layer composite insulation layer is simultaneously irradiated and crosslinked to form a three-dimensional crosslinked network. Among them, the crosslinking degree of the transition layer after irradiation is 45-55%, the crosslinking degree of the functional layer is 60-70%, and the crosslinking degree of the fire-resistant layer is 50-60%.

[0037] All raw materials used in the following examples are commercially available industrial products. Specifically, the ethylene-vinyl acetate copolymer (EVA) used is a grade with a VA content of 18-28 wt%; the polyolefin elastomer (POE) used is a grade with a Mooney viscosity (ML(1+4)) of 5-30 at 100°C; the irradiated crosslinked polyolefin elastomer used is a grade of POE modified by irradiation crosslinking; the ethylene-butyl acrylate copolymer (EBA) contains 17-30 wt% butyl acrylate; and the silane-grafted polyolefin is vinyltrimethoxysilane-grafted polyethylene with a grafting rate of 1.0-2.5 wt%. The softening point of the low-melting-point borosilicate glass powder is 450-550℃, and the particle size is 5-15μm; the phosphorus-nitrogen synergistic flame retardant is a mixture of piperazine pyrophosphate and melamine polyphosphate in a mass ratio of 1:1-3:1; the crosslinking sensitizer is triallyl isocyanurate (TAIC); the compatibilizer is maleic anhydride-grafted polyolefin; the composite antioxidant is a mixture of hindered phenolic antioxidants and phosphite antioxidants; the anti-thermal-oxidative aging agent is an amine or phenolic antioxidant; the elastic toughening agent is a thermoplastic elastomer or liquid polybutadiene. Example

[0038] This embodiment provides a composite insulation layer structure and molding method for high-temperature resistant, low-smoke, halogen-free cables.

[0039] (I) Composite Insulation Layer Structure The conductor selected has a cross-sectional area of ​​2.5 mm². 2 Annealed copper conductor.

[0040] The transition layer has a thickness of 0.20 mm and its formulation is as follows, based on a total mass of 100 wt% for the transition layer: Ethylene-vinyl acetate copolymer-polyolefin elastomer blend matrix: 49.5 wt%, wherein the mass ratio of EVA to POE is 65:35; Vinyltrimethoxysilane grafted polyethylene: 10 wt%; Maleic anhydride grafted polyolefin compatibilizer: 4.5 wt%; Composite antioxidant: 1.5 wt%; Triallyl isocyanurate (TAIC): 1.5 wt%; Surface-activated aluminum hydroxide, which is surface-treated with a silane coupling agent and has an average particle size of 1-3 μm: 33 wt%.

[0041] The functional layer has a thickness of 0.8 mm and its formulation is as follows, based on a total functional layer mass of 100 wt%: Irradiated crosslinked polyolefin elastomer-ethylene-butyl acrylate copolymer blend resin: 42wt%, wherein the mass ratio of POE to EBA is 60:40; Phosphorus-nitrogen synergistic flame retardant, piperazine pyrophosphate and melamine polyphosphate in a mass ratio of 2:1: 7.5wt%; Surface-activated magnesium hydroxide and aluminum hydroxide compound, with magnesium hydroxide:aluminum hydroxide = 3:2 and an average particle size of 1-3μm: 44wt%; Anti-thermal oxidative aging agent: 1.5wt%; Triallyl isocyanurate (TAIC): 5wt%.

[0042] The refractory layer thickness is 0.30mm, and the refractory layer formula is as follows, based on a total refractory layer mass of 100wt%: Polyolefin elastomer matrix: 35wt%; Low melting point borosilicate glass powder with a softening point of 500℃ and a particle size of 5-15μm: 31wt%; Magnesium hydroxide and aluminum hydroxide compound with a magnesium hydroxide:aluminum hydroxide ratio of 1:1 and an average particle size of 1-3μm: 24wt%; Elastic toughening agent: 4.5wt%; Triallyl isocyanurate (TAIC): 5.5wt%.

[0043] (II) Molding Method S1. Three-layer co-extrusion molding: The components of the above-mentioned transition layer, functional layer and refractory layer are added to three single-screw extruders respectively. After plasticizing and melting, they are fed into the three-layer co-extrusion die head. Using a three-layer distributor, the components are co-extruded onto the conductor surface in one go at a co-extrusion temperature of 160℃ to form a three-layer composite insulation preform.

[0044] S2. Cooling and Shaping: The three-layer composite insulation layer blank obtained in S1 is gradually cooled in sections through an 80℃ warm water section and a 25℃ cold water section to obtain a three-layer composite insulation layer semi-finished product.

[0045] S3. Electron Beam Irradiation Crosslinking: The three-layer composite insulation semi-finished product obtained in S2 was subjected to simultaneous electron beam irradiation crosslinking using an electron accelerator at an irradiation dose of 100 kGy. The three layers of composite insulation simultaneously completed irradiation crosslinking, forming a three-dimensional crosslinked network. After irradiation, the degree of crosslinking of each layer was determined using gel extraction: the degree of crosslinking of the transition layer was 50%, the degree of crosslinking of the functional layer was 65%, and the degree of crosslinking of the refractory layer was 55%. Example

[0046] The difference between this embodiment and Embodiment 1 is that the formulations and thicknesses of the transition layer, functional layer, and refractory layer are different.

[0047] The transition layer has a thickness of 0.15 mm and its formulation is as follows, based on a total mass of 100 wt% for the transition layer: EVA-POE blend matrix (EVA:POE=60:40): 50wt%; Vinyltrimethoxysilane grafted polyethylene: 7wt%; Maleic anhydride grafted polyolefin compatibilizer: 6wt%; Composite antioxidant: 2wt%; TAIC: 2wt%; Surface-activated aluminum hydroxide: 33wt%.

[0048] The functional layer has a thickness of 0.4 mm and its formulation is as follows, based on a total functional layer mass of 100 wt%: Irradiated crosslinked POE-EBA blend resin (POE:EBA=50:50): 46wt%; Phosphorus-nitrogen synergistic flame retardant (piperazine pyrophosphate:melamine polyphosphate=1:1): 6wt%; Surface-activated magnesium hydroxide and aluminum hydroxide compound (magnesium hydroxide:aluminum hydroxide=3:2): 40wt%; Anti-thermal-oxidative aging agent: 2wt%; TAIC: 6wt%.

[0049] The refractory layer thickness is 0.40 mm, and the refractory layer formula is as follows, based on a total refractory layer mass of 100 wt%: Polyolefin elastomer matrix: 38wt%; Low melting point borosilicate glass powder with a softening point of 450℃ and a particle size of 5-15μm: 28wt%; Magnesium hydroxide and aluminum hydroxide compound (magnesium hydroxide: aluminum hydroxide = 1:1): 26wt%; Elastic toughening agent: 3wt%; TAIC: 5wt%.

[0050] In the molding method, the co-extrusion temperature in S1 is 140℃, and the irradiation dose in S3 is 80kGy. After irradiation, the crosslinking degrees of each layer are as follows: transition layer 45%, functional layer 60%, and refractory layer 50%. Example

[0051] The difference between this embodiment and Embodiment 1 is that the formulations and thicknesses of the transition layer, functional layer, and refractory layer are different.

[0052] The transition layer has a thickness of 0.30 mm and its formulation is as follows, based on a total mass of 100 wt% for the transition layer: EVA-POE blend matrix (EVA:POE=70:30): 49wt%; Vinyltrimethoxysilane grafted polyethylene: 12wt%; Maleic anhydride grafted polyolefin compatibilizer: 3wt%; Composite antioxidant: 1wt%; TAIC: 1wt%; Surface-activated aluminum hydroxide: 34wt%.

[0053] The functional layer has a thickness of 1.2 mm and its formulation is as follows, based on a total functional layer mass of 100 wt%: Irradiated crosslinked POE-EBA blend resin (POE:EBA=70:30): 38wt%; Phosphorus-nitrogen synergistic flame retardant (piperazine pyrophosphate:melamine polyphosphate=3:1): 9wt%; Surface-activated magnesium hydroxide and aluminum hydroxide compound (magnesium hydroxide:aluminum hydroxide=3:2): 48wt%; Anti-thermal-oxidative aging agent: 1wt%; TAIC: 4wt%.

[0054] The refractory layer thickness is 0.20mm, and the refractory layer formula is as follows, based on a total refractory layer mass of 100wt%: Polyolefin elastomer matrix: 32wt%; Low melting point borosilicate glass powder with a softening point of 550℃ and a particle size of 5-15μm: 34wt%; Magnesium hydroxide and aluminum hydroxide compound (magnesium hydroxide: aluminum hydroxide = 1:1): 22wt%; Elastic toughening agent: 6wt%; TAIC: 6wt%.

[0055] In the molding method, the co-extrusion temperature in S1 is 180℃, and the irradiation dose in S3 is 120kGy. After irradiation, the crosslinking degrees of each layer are as follows: transition layer 55%, functional layer 70%, and refractory layer 60%. Example

[0056] The difference between this embodiment and Embodiment 1 is that in the molding method, the S2 cooling and shaping adopts a one-step direct water cooling method, only passing through a 25°C cold water section, without using a segmented water cooling method. The remaining components, thickness, and process parameters are the same as in Embodiment 1. Example

[0057] The difference between this embodiment and Embodiment 1 is that in the molding method, the three-layer co-extrusion die head of S1 adopts a series die head instead of a three-layer distributor type. The remaining components, thickness, and process parameters are the same as in Embodiment 1.

[0058] Comparative Example 1 The difference between this comparative example and Example 1 is that no transition layer is provided; it consists only of a functional layer and a refractory layer, forming a double-layer structure, with the functional layer directly covering the conductor surface. The formulations and thicknesses of the functional layer and the refractory layer are the same as those of the functional layer and the refractory layer in Example 1. The molding method is a one-time co-extrusion molding of the double layer, and the remaining process parameters are the same as those in Example 1.

[0059] Comparative Example 2 The difference between this comparative example and Example 1 is that no silane-grafted polyolefin (vinyltrimethoxysilane-grafted polyethylene) is added to the transition layer; this portion is made up by an equal amount of EVA-POE blend matrix. All other components, thicknesses, and process parameters are the same as in Example 1.

[0060] Comparative Example 3 The difference between this comparative example and Example 1 is that the filling amount of the three layers of inorganic filler does not show a gradient increasing distribution. That is, the filling amount of inorganic filler in the transition layer is 44wt%, the filling amount of inorganic filler in the functional layer is 44wt%, and the filling amount of inorganic filler in the refractory layer is 44wt%. The three layers are filled equally, which is different from the gradient distribution of 33wt% in the transition layer, 44wt% in the functional layer, and 55.5wt% in the refractory layer in Example 1.

[0061] The adjustments were as follows: the aluminum hydroxide content in the transition layer was increased to 44 wt%, and the EVA-POE blend matrix content was correspondingly reduced; the total amount of glass powder and metal hydroxide in the refractory layer was reduced to 44 wt%, and the polyolefin elastomer matrix content was correspondingly increased. All other components, thicknesses, and process parameters remained the same as in Example 1.

[0062] Comparative Example 4 The difference between this comparative example and Example 1 is that the molding method S3 adopts a stepwise irradiation crosslinking method. That is, the three-layer composite insulation layer after extrusion is first subjected to irradiation crosslinking at a dose of 50 kGy; then the semi-finished product is subjected to irradiation crosslinking at a dose of 50 kGy; the total dose is still 100 kGy, but it is not a one-time simultaneous crosslinking. The remaining components, thickness and process parameters are the same as in Example 1.

[0063] Comparative Example 5 The difference between this comparative example and Example 1 is that low-melting-point borosilicate glass powder is not added to the refractory layer. This part of the mass is made up by an equal amount of polyolefin elastomer matrix, that is, the content of polyolefin elastomer matrix in the refractory layer is 66wt%, metal hydroxide is 24wt%, elastic toughening agent is 4.5wt%, and TAIC is 5.5wt%. The remaining components, thickness and process parameters are the same as in Example 1.

[0064] The cable samples prepared in Examples 1-5 and Comparative Examples 1-5 were subjected to the following performance tests: 1. Interface bonding strength test The test was conducted in accordance with GB / T 2790-1995 "Test Method for 180° Peel Strength of Adhesives - Flexible Materials vs. Rigid Materials". Cable samples from each example and comparative example were taken, and the insulation layer was cut and peeled off along the axial direction. The 180° peel strength (N / cm) between each layer was recorded to evaluate the interlayer bonding strength.

[0065] 2. Hot and cold alternating cycle test The test was conducted according to GB / T 2423.22-2012 "Environmental Testing - Part 2: Test Methods - Test N: Temperature Change". The cable sample was cycled 100 times between -40℃ (held for 2 hours) and 125℃ (held for 2 hours), with each cycle lasting no more than 5 minutes. After the cycle, the insulation cross-section was observed under a 50x optical microscope to check for defects such as interlayer microcracks and delamination.

[0066] 3. Fire resistance test The test was conducted in accordance with GB / T 19216.21-2003 "Line Integrity Tests for Cables or Optical Fibers under Flame Conditions - Part 21: Test Procedures and Requirements for Cables with Rated Voltages of 0.6 / 1.0kV and Below". The cable samples were burned at a flame temperature of 750-800℃ for 90 minutes, and the integrity of the line was recorded, i.e., whether breakdown or open circuit occurred.

[0067] 4. Flame spread test Place the cable sample vertically and apply a flame (temperature about 750℃) to the lower end with a propane torch for 15 minutes. Observe whether the flame spreads longitudinally along the cable surface and whether the insulation layer melts and drips, igniting the lower filter paper.

[0068] 5. Bending performance test The low-temperature bending test was conducted in accordance with GB / T 2951.14-2008 "General Test Methods for Insulation and Sheath Materials of Cables and Optical Cables - Part 14: General Test Methods - Low Temperature Test". The cable was bent 180° around a test bar of specified diameter at -25°C, and the surface of the insulation layer was observed to see if cracks appeared.

[0069] 6. Volume resistivity test According to GB / T 1410-2006 "Test Methods for Volume Resistivity and Surface Resistivity of Solid Insulating Materials", the volume resistivity (Ω·cm) of the insulation layer was tested under high temperature conditions of 125℃.

[0070] 7. Limiting Oxygen Index (LOI) Test Referring to GB / T 2406.2-2009 "Determination of Combustion Behavior by Oxygen Index Method for Plastics - Part 2: Room Temperature Test", the limiting oxygen index (%) of the insulating layer material was tested.

[0071] The test results for each embodiment and comparative example are shown in the table below: Interfacial peel strength (N / cm) 28.5 25.3 26.8 22.1 27.9 12.6 8.4 27.2 28.1 28.3 Microcracks after 100 cycles of hot and cold cycling none none none A few microcracks none Multiple microcracks Interlayer stratification none none none Fire resistance pass pass pass pass pass pass pass Not passed pass Not passed Flames burst into flames No cross-ignition No cross-ignition No cross-ignition No cross-ignition No cross-ignition No cross-ignition No cross-ignition No cross-ignition No cross-ignition There is a possibility of crossfire. -25℃ bending none none none none none none none Cracks none none Volume resistivity at 125℃ (Ω·cm) <![CDATA[2.8×10 13 ]]> <![CDATA[2.1×10 13 ]]> <![CDATA[2.5×10 13 ]]> <![CDATA[2.6×10 13 ]]> <![CDATA[2.7×10 13 ]]> <![CDATA[2.6×10 13 ]]> <![CDATA[2.4×10 13 ]]> <![CDATA[1.8×10 13 ]]> <![CDATA[2.5×10 13 ]]> <![CDATA[2.7×10 13 ]]> Limiting oxygen index (%) 36.5 34.2 35.8 36.2 36.3 36.1 36.2 32.5 36.4 29.6 Analysis of the test results shows that: 1. Interfacial bonding strength and reliability under thermal cycling The test results in the table above show that the interfacial peel strength of Examples 1-5 ranged from 22.1 to 28.5 N / cm, which were significantly higher than those of Comparative Example 1 (12.6 N / cm) and Comparative Example 2 (8.4 N / cm). No interlayer microcracks or delamination defects were observed in Examples 1-5 after 100 cycles of thermal cycling from -40℃ to 125℃; however, Comparative Example 1 (without bilayer interfacial reinforcement design) showed multiple microcracks, and Comparative Example 2 (without silane-grafted polyolefin in the transition layer) showed interfacial delamination. This indicates that the silane-grafted polyolefin in the transition layer undergoes a chemical bonding reaction with the polymer chains of adjacent layers under high co-extrusion conditions, forming an interfacial bridging effect; simultaneously, the EVA-POE blend matrix endows the transition layer with excellent elastic deformation capacity, effectively absorbing and buffering the interfacial shear stress caused by differences in thermal expansion. Comparative Example 4 adopted a stepwise irradiation crosslinking method. The interfacial peel strength (28.1 N / cm) was comparable to that of Example 1, but a small number of microcracks appeared after the alternation of hot and cold. This indicates that stepwise irradiation may cause microstructural changes at the interlayer interface between two irradiations, while simultaneous irradiation is beneficial for the three layers to form a synergistic three-dimensional crosslinking network, and the interfacial bonding is more uniform and stable.

[0072] 2. Fire resistance and flame spread protection As shown in the table above, Examples 1-5 all passed the 750℃×90min fire resistance test without flame propagation, while Comparative Example 5 (the fire resistance layer does not contain low-melting-point borosilicate glass powder) failed the fire resistance test and exhibited flame propagation. This indicates that the low-melting-point borosilicate glass powder in the fire resistance layer melts under high-temperature flames to form a dense ceramic protective layer, effectively isolating heat and oxygen from being transferred to the interior, thus enabling the insulation layer to possess inherent fire resistance. Simultaneously, the three-layer integrated structure eliminates physical gaps between layers, preventing longitudinal flame propagation channels. Although Comparative Example 3 contains glass powder, the inorganic filler content in the three layers is equal, yet it failed the fire resistance test. This demonstrates that high filler content (50-58 wt%) in the outer layer is the material basis for ensuring ceramic shell formation; if the filler content is insufficient, the ceramic layer density is insufficient, and flame heat can still penetrate the insulation layer, leading to breakdown.

[0073] 3. Flexibility The results of the -25℃ low-temperature bending test showed that no cracks appeared in Examples 1-5, while cracks appeared in Comparative Example 3 (three layers of inorganic filler evenly filled). This indicates that the design of the inorganic filler gradient from the inside to the outside of this application ensures that the inner and functional layers retain sufficient polymer elastic matrix to guarantee flexibility, while the outer layer concentrates a high-filling inorganic system to achieve fire resistance, effectively solving the problem of material hardness and brittleness and low-temperature cracking caused by high-filling inorganic filler.

[0074] 4. High-temperature electrical insulation performance The volume resistivity of Examples 1-5 at 125℃ all reached 2.1×10⁻⁶. 13 Above Ω·cm, in Comparative Example 3, the uniform filling of inorganic fillers led to an increase in interface and matrix defects, resulting in a decrease in volume resistivity to 1.8 × 10⁻⁶. 13 Ω·cm. This indicates that the synergistic combination of the irradiated cross-linked POE-EBA blend resin, phosphorus and nitrogen synergistic flame retardant, and metal hydroxide in the functional layer ensures the insulation retention rate at high temperatures.

[0075] 5. Flame retardant properties The limiting oxygen index of Examples 1-5 all reached over 34%, which was better than that of Comparative Example 3 (32.5%) and Comparative Example 5 (29.6%). This indicates that the synergistic flame retardancy of phosphorus and nitrogen in the functional layer and the synergistic flame retardancy of ceramicization in the refractory layer achieved excellent flame retardant effect.

[0076] In summary, the composite insulation layer structure for high-temperature resistant, low-smoke, halogen-free cables prepared in the embodiments of this application achieves significant technical effects in terms of interface bonding strength, thermal cycling reliability, fire resistance, flexibility, and high-temperature electrical insulation performance through the comprehensive synergy of the silane grafting interface enhancement of the transition layer, the gradient increase of the three layers of inorganic fillers, the ceramicized body fire resistance of the fire-resistant layer, and the three-layer synchronous co-extrusion-synchronous irradiation crosslinking process. It solves the technical problems of weak interface bonding, easy delamination, poor flexibility under high filler and fire risk in the prior art, and is suitable for application scenarios with stringent requirements for cable performance, such as new energy, rail transit, and special equipment.

Claims

1. A composite insulation layer structure for high-temperature resistant, low-smoke, halogen-free cables, covering the outside of the conductor, characterized in that: The composite insulation layer structure consists of a transition layer, a functional layer, and a refractory layer from the inside out, forming an integrated composite insulation layer structure. Each layer of the composite insulation layer structure is a halogen-free polymer extrusion layer. No mica refractory wrapping layer is provided on the outer side of the composite insulation layer structure. The transition layer comprises an ethylene-vinyl acetate copolymer-polyolefin elastomer blend matrix, a silane-grafted polyolefin, and a first inorganic filler; The functional layer comprises an irradiated cross-linked polyolefin elastomer-ethylene-butyl acrylate copolymer blend resin, a phosphorus-nitrogen synergistic flame retardant, and a second inorganic filler; The refractory layer comprises a polyolefin elastomer matrix and a third inorganic filler, wherein the third inorganic filler comprises low-melting-point borosilicate glass powder and metal hydroxide; The composite insulation layer structure consists of three layers of inorganic fillers with gradually increasing amounts from the inside out. Based on the total mass of each layer, the first inorganic filler accounts for 25-35 wt% of the total mass of the transition layer, the second inorganic filler accounts for 40-48 wt% of the total mass of the functional layer, and the third inorganic filler accounts for 50-58 wt% of the total mass of the refractory layer.

2. The composite insulation layer structure for high-temperature resistant, low-smoke, halogen-free cables according to claim 1, characterized in that: The thickness of the transition layer is 0.15-0.30 mm, the thickness of the functional layer is 0.4-1.2 mm, and the thickness of the fire-resistant layer is 0.2-0.4 mm.

3. The composite insulation layer structure for high-temperature resistant, low-smoke, halogen-free cables according to claim 1, characterized in that: The first inorganic filler is surface-activated aluminum hydroxide; by weight percentage, the transition layer comprises the following components: 42-50 wt% ethylene-vinyl acetate copolymer-polyolefin elastomer blend matrix, 7-12 wt% silane-grafted polyolefin, 3-6 wt% compatibilizer, 1-2 wt% composite antioxidant, 1-2 wt% crosslinking sensitizer, and 25-35 wt% surface-activated aluminum hydroxide; wherein, the mass ratio of ethylene-vinyl acetate copolymer to polyolefin elastomer in the ethylene-vinyl acetate copolymer-polyolefin elastomer blend matrix is ​​60:40-70:30, and the silane-grafted polyolefin is vinyltrimethoxysilane-grafted polyethylene.

4. The composite insulation layer structure for high-temperature resistant, low-smoke, halogen-free cables according to claim 1, characterized in that: The second inorganic filler is a magnesium hydroxide and aluminum hydroxide compound with a mass ratio of magnesium hydroxide to aluminum hydroxide of 3:2; by weight percentage, the functional layer comprises the following components: 38-46 wt% of irradiated crosslinked polyolefin elastomer-ethylene-butyl acrylate copolymer blend resin, 6-9 wt% of phosphorus-nitrogen synergistic flame retardant, 40-48 wt% of surface-activated magnesium hydroxide and aluminum hydroxide compound, 1-2 wt% of anti-thermal-oxidative aging agent, and 1-2 wt% of crosslinking sensitizer; wherein, the mass ratio of polyolefin elastomer to ethylene-butyl acrylate copolymer in the polyolefin elastomer-ethylene-butyl acrylate copolymer blend resin is 50:50-70:30, and the phosphorus-nitrogen synergistic flame retardant is a compound of piperazine pyrophosphate and melamine polyphosphate.

5. The composite insulation layer structure for high-temperature resistant, low-smoke, halogen-free cables according to claim 1, characterized in that: The metal hydroxide in the refractory layer is a magnesium hydroxide and aluminum hydroxide compound with a mass ratio of magnesium hydroxide to aluminum hydroxide of 1:

1. By weight percentage, the refractory layer comprises the following components: 32-38 wt% polyolefin elastomer matrix, 28-34 wt% low-melting-point borosilicate glass powder, 22-26 wt% magnesium hydroxide and aluminum hydroxide compound, 3-6 wt% elastic toughening agent, and 1-3 wt% crosslinking sensitizer; wherein the low-melting-point borosilicate glass powder has a softening point of 450-550℃ and a particle size of 5-15 μm.

6. A molding method for preparing a composite insulation layer structure for high-temperature resistant, low-smoke, halogen-free cables as described in any one of claims 1-5, characterized in that, Includes the following steps: S1. The components used to prepare the transition layer, functional layer and refractory layer are co-extruded onto the conductor surface in one step through a three-layer co-extrusion die head to form a three-layer composite insulation layer preform. S2. Cool and shape the three-layer composite insulation layer blank obtained in S1 to obtain a three-layer composite insulation layer semi-finished product. S3. The three-layer composite insulation layer semi-finished product obtained in S2 is subjected to three-layer synchronous electron beam irradiation crosslinking. The three-layer composite insulation layer is simultaneously irradiated and crosslinked to form a three-dimensional crosslinked network. Among them, the crosslinking degree of the transition layer after irradiation is 45-55%, the crosslinking degree of the functional layer is 60-70%, and the crosslinking degree of the fire-resistant layer is 50-60%.

7. The molding method according to claim 6, characterized in that: In S1, the three-layer co-extruder is either a series type or a three-layer distributor type, and the co-extrusion temperature of the three-layer co-extruder head is 140-180℃.

8. The molding method according to claim 6, characterized in that: In S2, the cooling and shaping process adopts a segmented water cooling method, which involves gradually cooling the water by passing through an 80°C warm water section and a 25°C cold water section.

9. The molding method according to claim 6, characterized in that: In S3, by using the same type of crosslinking sensitizer but with different amounts in the formulations of the transition layer, functional layer and refractory layer, the three-layer composite insulation layer can obtain different degrees of crosslinking; the crosslinking sensitizer is triallyl isocyanurate.

10. The molding method according to claim 6, characterized in that: In S3, the irradiation dose of the three-layer synchrotron electron beam crosslinking is 80-120 kGy.

Citation Information

Patent Citations

  • High temperature resistant bilayer is crowded low smoke and zero halogen fire prevention crosslinked electric wire altogether

    CN208444644U

  • Halogen-free low-smoke high-performance wire

    CN212010402U

  • Low-smoke fire-resistant flame-retardant cable for rail transit

    CN215496123U